Minimally invasive versus open pancreatic surgery: meta-analysis of randomized clinical trials - Pfister, Matthias; Probst, Pascal; Müller, Philip C.; Antony, Pia-Anita; Klotz, Rosa; Kalkum, Eva; Merz, Daniela; Renzulli, Pietro Alexander; Hauswirth, Fabian; Müller, Markus K. (BJS open, 2023)
Widespread implementation of the minimally invasive technique in pancreatic surgery has proven to be challenging. The aim of this study was to compare the perioperative outcomes of minimally invasive (laparoscopic and robotic) pancreatic surgery with open pancreatic surgery using data obtained from RCTs.A literature search was done using Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, and Web of Science; all available RCTs comparing minimally invasive pancreatic surgery and open pancreatic surgery in adults requiring elective distal pancreatectomy or partial pancreatoduodenectomy were included. Outcomes were mortality rate, general and pancreatic surgery specific morbidity rate, and length of hospital stay.Six RCTs with 984 patients were included; 99.0 per cent (486) of minimally invasive procedures were performed laparoscopically and 1.0 per cent (five) robotically. In minimally invasive pancreatic surgery, length of hospital stay (−1.3 days, −2 to −0.5, P = 0.001) and intraoperative blood loss (−137 ml, −182 to −92, P < 0.001) were reduced. In the subgroup analysis, reduction in length of hospital stay was only present for minimally invasive distal pancreatectomy (−2 days, −2.3 to −1.7, P < 0.001). A minimally invasive approach showed reductions in surgical site infections (OR 0.4, 0.1 to 0.96, P = 0.040) and intraoperative blood loss (−131 ml, −173 to −89, P < 0.001) with a 75 min longer duration of surgery (42 to 108 min, P < 0.001) only in partial pancreatoduodenectomy. No significant differences were found with regards to mortality rate and postoperative complications.This meta-analysis presents level 1 evidence of reduced length of hospital stay and intraoperative blood loss in minimally invasive pancreatic surgery compared with open pancreatic surgery. Morbidity rate and mortality rate were comparable, but longer duration of surgery in minimally invasive partial pancreatoduodenectomy hints that this technique in partial pancreatoduodenectomy is technically more challenging than in distal pancreatectomy.
Gesehen am 25.05.2023